2020
DOI: 10.2196/18857
|View full text |Cite
|
Sign up to set email alerts
|

Development of an International, Multicenter, Hyperbaric Oxygen Treatment Registry and Research Consortium: Protocol for Outcome Data Collection and Analysis

Abstract: Background Hyperbaric oxygen (HBO2)—oxygen at pressures higher than atmospheric—is approved for 14 indications by the Undersea and Hyperbaric Medical Society. HBO2’s main effect is to increase oxygen content in plasma and body tissues, which can counteract hypoxia or ischemia. Laboratory studies show that HBO2 has effects beyond relieving hypoxia (eg, promoting angiogenesis in irradiated tissue, anti-inflammatory effects, radiosensitization of tumors, hypoxia preconditioning, and fungal growth inhi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…Soft tissue injuries, wound healing, and underwater medicine are only a few of the indications for HBOT. 6 , 31 recent research has revealed that hyperbaric oxygen treatment is effective in the treatment of a number of ailments. The development of a patient information registration system for undersea medicine and HBOT could be advantageous.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Soft tissue injuries, wound healing, and underwater medicine are only a few of the indications for HBOT. 6 , 31 recent research has revealed that hyperbaric oxygen treatment is effective in the treatment of a number of ailments. The development of a patient information registration system for undersea medicine and HBOT could be advantageous.…”
Section: Discussionmentioning
confidence: 99%
“… 32 Accuracy and completeness of data are the most critical factors affecting the quality and value of any registration system. 6 , 16 , 31 , 32 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Dartmouth–Hitchcock Institutional Review Board (IRB) approved this retrospective chart review, and collected data were deidentified as mandated. A list of all patients with diabetes mellitus at the Dartmouth–Hitchcock Medical Center who underwent hyperbaric oxygen therapy (HBOT) was obtained from the institutional HBOT registry [ 7 ]. Data on proteinuria, serum creatinine, use of angiotensin-converting enzyme inhibitors (ACEIs), and use of angiotensin receptor blockers (ARBs) was obtained from electronic medical records.…”
Section: Methodsmentioning
confidence: 99%
“…Hyperbaric oxygen therapy (HBO 2 ) is defined as breathing close to 100% oxygen in a hyperbaric oxygen chamber, where the pressure exceeds 1.4 absolute atmospheres (ATA). 21 HBO 2 therapy is performed in 2–3 absolute atmospheric pressure chambers 2–3 times daily. The length of treatment varies according to distinct indications but is usually between 1.5 and 2 hours.…”
Section: Introductionmentioning
confidence: 99%